Implementasi Membangun Strategi Budaya Organisasi - Wustari L. Mangundjaya; Ratri E. Yuniarso; Dela Tri Wulan Ningrum; Sheilin Dwi Agustin (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Organizational culture is a key values that are believed and contain characteristics that are brought by members of the organization into their organization, which then make a value system at different intensities and gives it a different identity, so that the organization has a personality as a system that is shared and will create an effective organization with a strong culture and is different from other organizations. To achieve a good internalization of the values, is a long process, started from socialization. The aimed of this research is to identify the process of developing organizational culture at PT X, that manufacturing car’s engines. The method used by qualitative research using interview, observation, discission and internal data (secondary data). The current stage of the program is under the awareness and understanding, thus still need a long process and intervention to the stage of internalization.